Adiponectin, blood pressure and hypertension - Ivković, Vanja (Array, 2019)
Adipokines, cytokines derived from adipose tissue, not only herald and confirm fat tissue as the largest endocrine organ but are also associated with a number of pathological states including obesity, insulin resistance and diabetes. There is a growing body of research on the role of adipokines in blood pressure regulation and development of hypertension. One of these adipokines, adiponectin, is especially interesting, given that it has numerous beneficial effects which include increasing insulin sensitivity and antiatherogenic and anti-inflammatory effects. In recent years, there has been a number of studies examining its possibly protective role in hypertension. In this narrative review we summarize the evidence on the association of adiponectin and polymorphism of the gene which encodes it with blood pressure levels and risk of hypertension, which might provide ideas for future research of adiponectin as a biomarker and potential therapeutic target in this condition.